2009
DOI: 10.1200/jco.2008.21.7125
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Biomarker Study of ABT-869, a Multiple Receptor Tyrosine Kinase Inhibitor, in Patients With Refractory Solid Malignancies

Abstract: ABT-869 by continuous once-daily dosing was tolerable at doses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 27 publications
5
65
0
Order By: Relevance
“…Studies done previously have shown linifanib as an inhibitor of PI3K/AKT, mitogen-activated protein kinase pathways in acute myeloid leukemia [36,37] and also the expression of VEGF in several types of cancers. [38,39] The combination of linifanib with radiation has shown better results than either of them being employed alone according to the preliminary data available.…”
Section: Motesanibmentioning
confidence: 96%
“…Studies done previously have shown linifanib as an inhibitor of PI3K/AKT, mitogen-activated protein kinase pathways in acute myeloid leukemia [36,37] and also the expression of VEGF in several types of cancers. [38,39] The combination of linifanib with radiation has shown better results than either of them being employed alone according to the preliminary data available.…”
Section: Motesanibmentioning
confidence: 96%
“…Linifanib showed single agent in several tumours including non-small lung cancer, CRC, ovarian cancer, hepatocellular carcinoma, neuroendocrine tumor, renal cell carcinoma and alveolar soft part sarcoma [49]. Very recently, linifanib added to standard platinum-based chemotherapy showed to be safe and active in non-squamous NSCLC patients [50].…”
Section: Linifanibmentioning
confidence: 99%
“…Two patients in study M06-879 had received drug treatment every other day rather than every day. [9] Phase I : Analysis of preliminary results from a phase I trial of linifanib showed that 15 patients exhibited adverse events of grade 2 or higher; hypertension (12); neutropenia (4), thrombocytopenia (3), and hand foot syndrome (2). Two patients experienced a dose limiting toxicity; one each of grade 3 ALT increase at 0.10 mg/kg and ECG T-wave inversion at 0.25 mg/kg.…”
Section: Solid Tumorsmentioning
confidence: 99%
“…Hypertension and proteinuria were reversible on dose interruption. [12,13] In a phase I trial in patients who continued treatment with linifanib for >1 year, the common adverse events were myalgia and fatigue. Grade 3 adverse events related to linifanib were fatigue, abdominal pain, and palmar-plantar erythrodysesthesia.…”
Section: Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation